Implementation of the Educational Intervention Program to Improve the Quality of Learning at SD Negeri 018 Galang - Sharla Aulia Rizki; Suryo Hartanto; Yesi Gusmania (Journal of Educational Sciences, 2026)
The educational intervention program integrates theoretical knowledge with classroom practice at SD Negeri 018 Galang. This study examined the effect of a problem-based learning (PBL) model on students’ literacy and numeracy skills. A pre-test and post-test experimental design was employed with a sample of 15 students. The instruments consisted of expert-validated literacy and numeracy tests. Data were analyzed using normality tests, Wilcoxon signed ranks tests, and paired sample t-tests. The pre-test results indicated that literacy scores were not normally distributed (p = 0.010), while post-test literacy scores showed a normal distribution (p = 0.165). Numeracy scores, both before and after the intervention, were normally distributed. Of the 15 participants, 12 students experienced a decline in literacy scores (Z = −2.458, p = 0.014). A significant difference was found between pre-test and post-test scores (t = −3.287, p = 0.005), suggesting the need for careful evaluation of the learning model. Overall, the findings revealed a decrease in literacy outcomes, indicating that the applied strategies require adjustment to better support learning. In contrast, numeracy outcomes showed significant improvement, reflecting effective problem-based learning through contextual activities and educational games related to daily experiences.